The Effect Of The Banking Activity Of The Economic Growth : Case In Indonesia - et. al., Lia Amaliawiati, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The objective of this study is to examine the impact of banking activities on Indonesia's economic growth (Gt) in both the short and long term. Banking activity variables are related to bank (CR) and savings (S) domestic credit to the private sector, while other independent variables that can influence economic growth are capital (CAP) and labor force (L). This study uses data from time series for the period 1993-19. The first step is to test the stationarity of the data with the root test unit and the results are only stationary data with the first difference. In addition, the co-integration test between the variables and the results shows a co-integration relationship between the variables so that the model can be analyzed using the Error Correction Model (ECM) to see the short-term balance. The results of the ECM model analysis show that lending banking does not have an impact on economic growth in the short term, but on economic growth in the long term, while saving affects both short-term and long-term economic growth. Other variables indicate that the capital variable has no effect on economic growth in the short and long term, while the labor variable affects economic growth only in the long term, While the labor variable affects economic growth only in the longer term, it has no effect in the short term.